2017
DOI: 10.1002/ecy.1915
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific variation shapes community‐level behavioral responses to urbanization in spiders

Abstract: Urban areas are an extreme example of human-changed environments, exposing organisms to multiple and strong selection pressures. Adaptive behavioral responses are thought to play a major role in animals' success or failure in such new environments. Approaches based on functional traits have proven especially valuable to understand how species communities respond to environmental gradients. Until recently, they have, however, often ignored the potential consequences of intraspecific trait variation (ITV). When … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 73 publications
3
34
0
Order By: Relevance
“…observations). Interestingly, while other orb-weaver species-especially the larger ones-showed dramatic declines in both abundance and species richness along an urbanization gradient [59,60], A. diadematus was found to reach similar low densities across this land-use gradient. In other words, local densities at spatial scales of approx.…”
Section: Discussionmentioning
confidence: 95%
“…observations). Interestingly, while other orb-weaver species-especially the larger ones-showed dramatic declines in both abundance and species richness along an urbanization gradient [59,60], A. diadematus was found to reach similar low densities across this land-use gradient. In other words, local densities at spatial scales of approx.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, while other orb-weaver speciesespecially the larger onesshowed dramatic declines in both abundance and species richness along an urbanisation gradient [53,54], A. diadematus was found to reach similar low densities across this land-use gradient. Or put conversely, local densities at spatial scales of approximately 100 km were alarmingly low in both the more natural and human impacted regions, demonstrating regional declines beyond the scale of local land-use.…”
Section: Discussionmentioning
confidence: 94%
“…Orb‐web spiders may shift web decorating behaviours and web width in response to ambient illumination containing UV wavelengths (Elgar et al, ), although behavioural responses to LED lights, which lack UV light, are untested. Dahirel, Dierick, Cock, and Bonte () found that spiders alter their web architecture to increase prey capture rates in response to shifts in the types of prey available in urban areas. However, they did not investigate such shifts in relation to artificial lights, which alter insect community composition (Davies, Bennie, & Gaston, ), and hence prey availability.…”
Section: Discussionmentioning
confidence: 99%